2021
DOI: 10.1002/fam.2999
|View full text |Cite
|
Sign up to set email alerts
|

Ignition temperature of combustible liquids in mixtures of air with nitrous oxide

Abstract: Summary While ignition temperatures in the air are well known for a large number of flammable substances and to a lesser extent in pure oxygen too, no such values exist for ignition temperatures in nitrous oxide in spite of the fact that nitrous oxide is used as oxidizer in combustion processes or aerosol propellant in industry. The ignition temperatures of some pure compounds have now been investigated in oxidizer mixtures of nitrous oxide and air with varying concentration of nitrous oxide up to 80 vol% usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Later, a comparative study, conducted by Deng et al using a high-pressure shock tube, refers to the influence of N 2 O and O 2 on ignition delay times of C 2 H 4 /O 2 /N 2 O/Ar and C 2 H 4 /N 2 O/Ar mixtures. Furthermore, Mitu et al , reported data about the ignition temperature of mixtures of combustible liquids with air enriched with O 2 or N 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a comparative study, conducted by Deng et al using a high-pressure shock tube, refers to the influence of N 2 O and O 2 on ignition delay times of C 2 H 4 /O 2 /N 2 O/Ar and C 2 H 4 /N 2 O/Ar mixtures. Furthermore, Mitu et al , reported data about the ignition temperature of mixtures of combustible liquids with air enriched with O 2 or N 2 O.…”
Section: Introductionmentioning
confidence: 99%